Interventions for Strengthening General Self-Efficacy Beliefs in College Students: An Integrative Review - Lais Palotta Balderrama Gueroni; Daniele Alcalá Pompeo; Letícia Palota Eid; Marcos Antonio Ferreira Júnior; Carlos Alberto da Cruz Sequeira; Luciano Garcia Lourenção (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To assess the evidence regarding the effectiveness of interventions aimed at strengthening self-efficacy beliefs in college students. Methods: Integrative Review conducted on the Lilacs, PubMed, CinahL, Cochrane Collaboration Databases, Scopus, and PsycInfo databases. The methodological quality of the studies was assessed using tools proposed by the Joanna Briggs Institute, and the results were analyzed descriptively. Results: Out of the 10 selected studies, six demonstrated that interventions aimed at strengthening self-efficacy were effective (Levels of Evidence II and III), and four revealed contrary results (Levels of Evidence I and II). Programs aimed at enhancing self-efficacy should include content on positive mental health, psychoeducation strategies, cover a period of eight to twelve weeks, and consider the completion of homework assignments. Conclusion: The synthesis of evidence pointed to pathways for building an effective self-efficacy strengthening program to be implemented in universities.